Cobalt Blues The Story of Leonard Grimmett, the Man Behind the First Cobalt-60 Unit in the United States - Almond, Peter R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
For the latter half of the 20th century, cobalt-60 units were the mainstay of radiation treatments for cancer. Cobalt Blues describes the development of the first cobalt-60 unit in the United States and the man behind it, Leonard Grimmett. Conceptually conceived before World War II, it only became possible because of the development of nuclear reactors during the war. Although Grimmett conceived of and published his ideas first, the Canadians built the first units because of the capability of their reactor to produce more suitable cobalt-60 sources. This book tells the story of how Grimmett and others came together at the time that the U S Atomic Energy Agency was pushing the use of radioactivity in medicine. Due to his sudden death, very little information about Grimmett was known until recently, when various documents have come to light, allowing the full story to be told.
Foreword -- Prologue -- M.D. Anderson Cancer Center 1941-1946 -- The Journey, January 29 to February 7, 1949 -- Early Life and Education, London 1903-1929 -- Medical Physicist Part I, London 1929-1944 -- The Unknown Years and UNESCO Paris, 1944-1948 -- Replacing Radium 1937-1949 -- Arrival, Houston February 1949 -- The Cobalt Unit 1949-1954 -- Medical Physicist Part II, Houston 1949-1951 -- Cobalt-60 and the Notebook -- Cobalt-60 in Perspective -- Epilogue: Grimmett the Man -- Appendix A: Principles of Radiotherapy -- Appendix B: Principles of Reactor Production of Cobalt-60 -- Appendix C: Grimmett$1 (Bs Suggested References on Cobalt-60.s
Keywords: Physics; Science -- History; Oncology; Radiology, Medical; Physics; Medical and Radiation Physics; History of Science; Diagnostic Radiology; Cancer Research